Relevansi Khutbah Jum`at Terhadap Upaya Menangkal Terorisme - - Junaidi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2006)
The article below traces how shalat Jum'at moment is very useful for public education and public transformation, especially forgiving them many perspectives on actual event and contemporer event. Shalat Jum'at as an Islamic ritual must be done by every muslim in masjid gives a chance for muslims to have a meeting once a week. A lot of muslims involve in this meeting. So that, shalat Jum'at event is a very good opportunity for khatib to transfer and transform the Islamic values to the community regularly. Khatib must choose the khutbah topic selectively. The article finds that shalat Jum'at event can be used for transforming peace values to community. It depends on two aspects, namely topic choosing by khatib and method of speech that must be delivered by comprehensive approach. The topic chooses that relevance to social context is a good topic to public education and public transformation.